2013
DOI: 10.5194/amt-6-3211-2013
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution chemical ionization mass spectrometry (ToF-CIMS): application to study SOA composition and processing

Abstract: This paper demonstrates the capabilities of chemical ionization mass spectrometry (CIMS) to study secondary organic aerosol (SOA) composition with a highresolution (HR) time-of-flight mass analyzer (aerosol-ToF-CIMS). In particular, by studying aqueous oxidation of water-soluble organic compounds (WSOC) extracted from α-pinene ozonolysis SOA, we assess the capabilities of three common CIMS reagent ions: (a) protonated water clusters (H 2 O) n H + , (b) acetate CH 3 C(O)O − and (c) iodide water clusters I(H 2 O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
206
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(213 citation statements)
references
References 52 publications
(81 reference statements)
6
206
0
1
Order By: Relevance
“…The relatively minor changes in O : C of SOA, despite modest changes in the SOA composition, suggest that there could be compensating effects, i.e., differences in SOA composition are offset by differences in the O : C of the SOA arising from low yield versus high yield pathways. Recently, high-resolution time-of-flight chemical ionization mass spectrometry (HRToF-CIMS) has been used to resolve the composition of SOA in carbon and oxidation state space (for ambient OA that is dominated by carbon, hydrogen and oxygen, oxidation state = 2× O : C − H : C) (Chhabra et al, 2015;Aljawhary et al, 2013). The SOM enables us to visualize the product distribution of SOA in carbon and oxygen space and allows for a direct comparison with the measurements.…”
Section: Soa In Carbon-oxygen Spacementioning
confidence: 99%
“…The relatively minor changes in O : C of SOA, despite modest changes in the SOA composition, suggest that there could be compensating effects, i.e., differences in SOA composition are offset by differences in the O : C of the SOA arising from low yield versus high yield pathways. Recently, high-resolution time-of-flight chemical ionization mass spectrometry (HRToF-CIMS) has been used to resolve the composition of SOA in carbon and oxidation state space (for ambient OA that is dominated by carbon, hydrogen and oxygen, oxidation state = 2× O : C − H : C) (Chhabra et al, 2015;Aljawhary et al, 2013). The SOM enables us to visualize the product distribution of SOA in carbon and oxygen space and allows for a direct comparison with the measurements.…”
Section: Soa In Carbon-oxygen Spacementioning
confidence: 99%
“…Acetate (CH 3 COO À ) reagent ions was used to ionize and detect acids, including peroxyacids [Veres et al, 2008;Lopez-Hilfiker et al, 2015]. Recent studies have also shown that this reagent ion can be used to measure polyphenols and nitrated phenols, benzoyl peroxide by proton abstraction with similar sensitivity as carboxylic acids [Mohr et al, 2013;Lopez-Hilfiker et al, 2015], and glyoxal, methylglyoxal, and levoglucosan, with far lower sensitivity, via clustering reactions [Veres et al, 2010;Aljawhary et al, 2013]. Since there was no biomass burning influence during BEACHON-RoMBAS, we assume that the contribution of phenols and levoglucosan to the particle-phase acid signal calculated here is minimal.…”
Section: Instrumentation 221 Movi-hrtof-cimsmentioning
confidence: 99%
“…The recent coupling of chemical ionization to high-resolution time-of-flight mass spectrometers (HR-ToF-MS) enables the simultaneous determination of the abundance and molecular composition of a wide array of atmospheric inorganic and organic compounds with fast time response and high sensitivity (Junninen et al, 2010;Bertram et al, 2011;Yatavelli et al, 2012;Aljawhary et al, 2013;Lee et al, 2014;Lopez-Hilfiker et al, 2014, 2016aFarmer, 2015, 2016;Yuan et al, 2016). The use of HR-ToF-CIMS has allowed for groundbreaking progress in atmospheric organic chemistry, such as the observation of 3610 Y.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many atmospheric organic systems consist of a wide range of organic compounds with different functionality and polarity. Therefore, multiple complementary ionization schemes are needed to obtain a broad view of these systems (Aljawhary et al, 2013;Praplan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation